EXPLORING THE ENGLISH PHRASES NEEDED AT THE TOURIST SITES IN PALOPO, SOUTH SULAWESI - Asmin, Arny Irhani (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2018)
English language is essential in the development of tourism. The English language for many years is used as an instructional language in the tourism industry. This paper aims at finding phrases that are needed at the local tourist sites and also to find out local people perspective related to the role of the English language in the tourism industry. This research is qualitative one and in collecting data the researcher applied direct observations and interviews. The results show that many English for tourism phrases in research sites are needed to know by the traders, hotel staff, officers, drivers and all people who live around the tourist sites in Palopo. The result of the study is expected to encourage people around the tourist sites and practitioners to pay attention to the issue of the English language in tourism. Improving collaboration between educational institutions and tourism organizations is needed in the sustainable development of the local tourism industry in Palopo.